Analysis of adverse events following immunization in Zhejiang, China, 2019: a retrospective cross-sectional study based on the passive surveillance system - Xuejiao Pan; Huakun Lv; Fuxing Chen; Ying Wang; Hui Liang; Linzhi Shen; Yaping Chen; Yu Hu (Human Vaccines & Immunotherapeutics, 2021)
Objectives: This study summarizes passive surveillance data for adverse events following immunization (AEFI) in Zhejiang province. Methods: The AEFI reports and number of doses on all vaccines used were extracted from the national AEFI surveillance system and the immunization information system of Zhejiang province (ZJIIS). Reporting rates of AEFI were calculated by age, city, severity of AEFI, categories of AEFI, vaccine types, and reaction categories. Results: A total of 13,079 AEFI records were reported and 23,091,401 vaccine doses were administered, with a reporting rate of 56.64/100,000 doses for AEFI. The highest reporting rate of AEFI was observed among the infants <1 year of age (108.61/100,000 doses) and the lowest rate was observed among recipients aged ≥60 years. Most of the AEFI reports were vaccine product-related reactions (48.81/100,000 doses), and the lowest was vaccination errors (0.02/100,000 doses). The most frequently reported individual vaccine was DTP and Hib combined vaccine, with a reporting rate of 426.62/100,000 doses. The most frequently reported AEFI was fever/redness/induration (48.82/100,000 doses). Conclusion: Our findings illustrated the high level of vaccine safety since the majority of those reported were not serious, or coincidentally associated with vaccination. Furthermore, the national AEFI surveillance system should be continuously used as a surveillance tool for monitoring of AEFI.